2023
DOI: 10.3389/fphar.2023.1136772
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue distribution of Ramulus Mori (Sangzhi) alkaloids in rats and its effects on liver enzyme activity

Abstract: Ramulus Mori (Sangzhi) alkaloids (SZ-A) derived from twigs of mulberry (Morus alba L., genus Morus in the Moraceae family) was approved by the National Medical Products Administration in 2020 for the treatment of type 2 diabetes mellitus. In addition to excellent hypoglycemic effect, increasing evidence has confirmed that SZ-A exerts multiple pharmacological effects, such as protecting pancreatic ß-cell function, stimulating adiponectin expression, and alleviating hepatic steatosis. Importantly, a specific dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The association of many of the CS compounds to cAMP targets such as ADORA1, HCAR2, and GABBR1 highlighted them among the genes in the cAMP pathway. Adenosine A1 receptor (ADORA1), a G protein-coupled receptor, inhibits the enzyme adenylate cyclase and plays a role in the regulation of cell metabolism and gene transcription, and therefore, has been identified as an important drug target for the treatment of various diseases and illnesses [75,76], including T2DM via glucose homeostasis and glucagon secretion regulation [77]. The identification of ADORA1 as a key target for T2DM and related complications (e.g., nephropathy) therapy buttresses previous studies (on morusin, kuwanon C, and morusyunnansin) from Morus alba (leaves) and Salvia miltiorhiza through NP and molecular docking analyses [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…The association of many of the CS compounds to cAMP targets such as ADORA1, HCAR2, and GABBR1 highlighted them among the genes in the cAMP pathway. Adenosine A1 receptor (ADORA1), a G protein-coupled receptor, inhibits the enzyme adenylate cyclase and plays a role in the regulation of cell metabolism and gene transcription, and therefore, has been identified as an important drug target for the treatment of various diseases and illnesses [75,76], including T2DM via glucose homeostasis and glucagon secretion regulation [77]. The identification of ADORA1 as a key target for T2DM and related complications (e.g., nephropathy) therapy buttresses previous studies (on morusin, kuwanon C, and morusyunnansin) from Morus alba (leaves) and Salvia miltiorhiza through NP and molecular docking analyses [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…Troxerutin also induced oxidative stress by elevating malondialdehyde concentration while reducing the activity levels of glutathione peroxidase and superoxide dismutase [140]. The anticancer properties of icariin have been documented in the literature [141][142][143][144][145][146]. The anticancer properties of icariin against human HeLa cervical cancer cell line and normal HCvEpC cells were assessed previously [146].…”
Section: Structural Similarity Search Of the Potential Candidatesmentioning
confidence: 99%
“…It was also demonstrated that SZ-As protected mice from HFD-mediated hepatic steatosis, triglyceride accumulation and adipose tissue inflammation, while the anti-inflammatory role appeared to depend on the blockage of p38 MAPK, ERK and JNK signaling pathway activation in macrophages [ 11 , 12 ]. Notably, tissue distribution analysis suggested that after oral administration, the major constituents of SZ-As are observed predominantly in the liver, followed by the adipose tissues [ 13 ], which revealed the potential regulating effects of SZ-As on liver and adipose tissue. So far, there are relatively few reports of the role of SZ-As in treating liver lipid metabolism disorder, and their therapeutic mechanism also remains unclear.…”
Section: Introductionmentioning
confidence: 99%